EKSTRAKSI GLUKOMANAN DARI TEPUNG PORANG (Amorphophallus muelleri Blume) DENGAN ETANOL - Nurlela Nurlela; Dewi Andriani; Ridha Arizal (Program Studi Kimia, Universitas Lambung Mangkurat, 2020)
Iles-Iles kuning (Amorphophallus muelleri Blume) is a potential source of glucomannan, a polysaccharide compound that has several special properties which often used in various fields of industry, pharmacy, and food. The quality of glucomannan produced domestically still cannot match the quality of imported glucomannan. This study aims to know the effect of difference extraction methods of glucomannan from iles-iles kuning flour using ethanol to obtain high contain of glucomannan with better quality. Good quality of glucomannan has high viscosity and contains small amount of water, ash, protein, fat, and starch. Extraction of iles-iles kuning flour using multilevel concentration of ethanol (40, 60, and 80%) was able to produce higher glucomannan and better quality than ethanol 60% with three times of extraction. Extraction using multilevel ethanol was able to improve glucomannan content from 16,43% to 62,2%. Fourier Transform Infra Red (FTIR) spectra of extracted glucomannan showed the functional groups composing the glucomannan compound (O-H, C=O, C-O, C-H) similar to the spectra of commercial glucomannan.